Hubungan Sarana dan Prasarana dengan Kinerja Tenaga Kesehatan Instalasi Gawat Darurat (IGD) di Masa Pandemi Covid-19 - Heni Fa'riatul Aeni; Muslimin Ali; Siti Milatul Zanah (STIKes Payung Negeri Pekanbaru, 2021)
Prevention of the transmission of the Corona-19 virus can be supported by improving adequate facilities and infrastructure according to standards which include Personal Protective Equipment) (PPE), especially health workers who are at the forefront of dealing with the Ovid-19 virus outbreak. There are still Emergency Room health workers at Cahaya Bunda Hospital who do not use PPE incompletely, including not using a 30% faceshield. The aim of the study is to determine the relationship of facilities and infrastructure with the performance of Emergency Room health workers in efforts to prevent and transmit the Covid-19 virus at RSIA Cahaya Bunda, Cirebon City the year 2021. The design of this study used a quantitative approach with cross sectional design, this population was 19 people from the Emergency Department RSIA Cahaya Bunda, Cirebon City, which obtained 19 samples of data as respondents. is a questionnaire checklist sheet, the data collection method uses primary data and secondary data and data analysis uses the Chi Square test.The results Chi Square test shows that there is a significant relationship between facilities and infrastructure and performance with a p-value of 0.003. Suggestions for health workers to further improve the performance of handling patients, and to use the facilities and infrastructure that have been provided optimally in an effort to prevent the transmission of Covid-19.